Social Media Problematic Use and Academic Procrastination: A Correlational Quantitative Study of Adolescents in Pakistan (Journal of Asian Development Studies, 2025)
Studies across the globe have shown not only the detrimental effects of social media problematic use on mental health but also on academic procrastination. However, there is a lack of comprehensive literature on the impact of social media problematic use on academic procrastination among adolescents, particularly in Pakistan. This study aims to investigate the association between social media problematic use and academic procrastination among adolescents aged 12 to 19 enrolled in private and public schools and colleges in Pakistan. A cross-sectional correlational research design was employed, using purposive sampling to collect data from 150 adolescents. Participants had to have used social media for at least one year. The Bergen Social Media Addiction Scale (BSMAS) and the Academic Procrastination Scale were used to assess the variables. Ethical guidelines in accordance with the APA’s 7th edition were strictly followed. Findings indicate a positive and significant relationship between social media problematic use and academic procrastination among adolescents in Pakistan. The study highlights the importance of developing interventions and educational policies aimed at reducing social media problematic use to improve academic outcomes.